THU0316 Update on the juvenile systemic sclerosis inception cohort. www.juvenilescleroderma.com. (23rd January 2014) - Foeldvari, I.; Ehlers, C.; Len, C.; Katsicas, M.M.; Tae, A.; Kalinich, T.; Kone-Paut, I.; Mouthon, L.; Uziel, Y.
Abstract : Background: Juvenile systemic sclerosis (jSSc) is a rare autoimmune disease. Currently just retrospective data exist without a standardized assessment of the organ involvement. Our project is the first projects, where prospectively and with a standardized assessment data of early jSSc patients are collected. Objectives: To learn about the evolvement of juvenile systemic sclerosis Methods: Using the proposed standardized patient assessment protocol patients with early jSSc, entry into the cohort within the first 24 months of disease, are prospectively assessed. All participating centres approved the protocol over the own IRB. Results: 50 centers from 20 countries applied to participate on the project. The assent and consent forms were translated into the local native languages. Up till now 16 patients were enrolled, who fulfilled the inclusion criteria. The mean follow up of the patients in the cohort are 1.9 years. 12 of the 16 patients were female. The age of onset of Raynaud symptomatic were 13.1 years The mean age at the onset of the non-Raynaud symptomatic were 13.2 years. Age at diagnosis at diagnosis was 13.5 years. 11 of the 16 have diffuse subtype, 5 of them have an overlap symptomatic. alle were ANA positive, and 6 of them were anti-Scl 70 positive. None of them was anticentromere positive. 15 of them have Raynaud's. None had renal crisis. Conclusions: We present the data on the first 16 prospectively assessed patients with jSSc. The current recruitment data confirms that pediatric patients are different from the adult patients. A large number of patients show overlap feutures. We are only at the first phase of this project and hope to recruit up to 50 patients and follow them prospectively over the next 2 to 4 years at least. Disclosure of Interest: None Declared